2021
DOI: 10.1121/10.0003354
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of roadway noise in a coastal city underwater soundscape during COVID-19 confinement

Abstract: Confinement due to the COVID-19 pandemic drastically reduced human activities. Underwater soundscape variations are discussed in this study, comparing a typical and confinement day in a coastal lagoon near a popular tourist city in Mexico. Recording devices were located at 2 m in depth and 430 m away from the main promenade—a two-way avenue for light vehicle traffic—where main tourist infrastructure is located. The nearby marine environment is habitat to birds and dolphins as well as fish and invertebrates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Ambient sound in the ocean is thought to have increased 3 dB per decade (Hildebrand, 2009): the same magnitude as the sound decrease reported in some of these articles over a few months' time. Studies published in other journals have also found reductions in sound levels due to the pandemic (Thomson and Barclay, 2020;León-López et al, 2021;Pine et al, 2021).…”
Section: Summary Of Covid-19 Papersmentioning
confidence: 94%
“…Ambient sound in the ocean is thought to have increased 3 dB per decade (Hildebrand, 2009): the same magnitude as the sound decrease reported in some of these articles over a few months' time. Studies published in other journals have also found reductions in sound levels due to the pandemic (Thomson and Barclay, 2020;León-López et al, 2021;Pine et al, 2021).…”
Section: Summary Of Covid-19 Papersmentioning
confidence: 94%
“…anthropophony) ( Slabbekoorn et al, 2010 ; Kight and Swaddle, 2011 ; Francis and Barber, 2013 ) were also observed (e.g. Asensio et al, 2020 ; Basu et al, 2021 ; Čurović et al, 2021 ; Leon-Lopez et al, 2021 ; Mostafa et al, 2021 ). The reduction of anthropogenic noise should make the natural soundscape, and particularly sounds produced by animals, i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Although substantial work has been conducted on freshwater species, predominantly on fishes and initially in aquaria (Gerald, 1971;Desjonquères et al, 2020;Grabowski et al, 2020;Linke et al, 2020;Roca et al, 2020;Higgs and Beach, 2021), the majority of efforts to record aquatic biological sounds have historically focused on the marine environment (Greenhalgh et al, 2020). Freshwater recordings present a variety of complexities that are less common in the marine environment, such as terrestrial, aerial and watersurface sounds from birds, insects, and road or air traffic (Erbe et al, 2018;Linke et al, 2020;Leon-Lopez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%